Efeitos farmacológicos do álcool sesquiterpênico (-)-α-bisabolol em preparações isoladas de músculo liso vasculares e não-vasculares - Siqueira, Rodrigo José Bezerra de (2011)
In this in vitro study the effects of the monocyclic sesquiterpene alcohol (-)-α-bisabolol on the contractile behavior of rat and mouse smooth muscle preparations were investigated. Under resting tonus, (-)-α-bisabolol relaxed duodenal smooth muscle preparations, whereas it showed biphasic effects in other smooth muscles, contracting endothelium-intact aortic rings and urinary bladder strips at the concentration range of 30 - 300 µM, and relaxing these tissues at higher concentrations. When applied on the steady state of sustained contractions, (-)-α-bisabolol showed only relaxing properties. It preferentially relaxed contractions induced electromechanically by a high extracellular concentration of K+ than those induced pharmacomechanically by adding phenylephrine or carbachol in the bath chamber. The pharmacological potency of (-)-α-bisabolol was variable being higher in mesenteric vessels, whereas it exerted relaxing activity with lesser potency on tracheal or colonic tissues. Tissues possessing spontaneous activity were also differentially influenced by (-)-α-bisabolol that completely decreased spontaneous contractions in duodenum whereas increased their amplitude in urinary bladder. The (-)-α-bisabolol showed more pronounced inhibitory effects on the concentration-effect curves induced by calcium or barium when constructed in presence of an agent producing eletromecanic coupling. The vasodilatory effect of (-)-α-bisabolol in aortic rings did not involve a role of endothelial factors or of potassium channels. In aortic preparations under calcium free conditions (-)-α-bisabolol augmented the phasic contractions induced by caffeine. In vivo, (-)-α-bisabolol attenuated the increased responses of carbachol in tracheal rings of ovalbumin-sensitized rats challenged with ovalbumin, but was without effect in the decreased responsiveness of urinary bladder strips in animals submitted to ifosfamide treatment. In summary, (-)-α-bisabolol is characterized as a biologically active substance on smooth muscle. At least part of the underlying mechanism involved in the (-)-α-bisabolol -induced inhibitory actions is related to its ability in reducing electromechanical coupling.